Oil spill removal using kenaf core fibers as biosorbent material - Siwayanan, P. (Institute of Physics Publishing, 2020)
Offshore crude oil exploration has led to oil spillage in the sea and causes an enormous negative impact on the surrounding environment, animals and human beings. In this paper, studies have been carried out to utilize Malaysian grown Kenaf core fibers as biosorbent material to clean-up the spilled oil from the sea. Kenaf fibers have natural oleophilic characteristics and therefore would be suitable to be used as biosorbent material. Studies were conducted to understand the surface characteristics, to evaluate the absorption capacity under simulated sea conditions and to determine oil/seawater sorption characteristics of Malaysia grown Kenaf core fibers. The crude oil/seawater absorption capacity study has indicated that both 20 mesh and 40 mesh Kenaf fibers can absorb 4 times its original weight in crude oil upon short contact time with crude oil/seawater. This study also reveals that the Kenaf fibers tend to absorb seawater upon prolonged contact with crude oil/seawater. Based on the separate crude oil and seawater sorption tests, both 20 mesh and 40 mesh Kenaf core fibers were found to have the ability to absorb 5-6 times and 1-6 times of its original weight in crude oil and seawater respectively, depending on the contact time. Â© 2020 IOP Publishing Ltd.